2020
DOI: 10.1519/jsc.0000000000003416
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and Body Composition Profile of Young Professional Soccer Players

Abstract: Bernal-Orozco, MF, Posada-Falomir, M, Quiñónez-Gastélum, CM, Plascencia-Aguilera, LP, Arana-Nuño, JR, Badillo-Camacho, N, Márquez-Sandoval, F, Holway, FE, and Vizmanos-Lamotte, B. Anthropometric and body composition profile of young professional soccer players. J Strength Cond Res 34(7): 1911–1923, 2020—The purpose was to describe the anthropometric and body composition profile of young professional soccer players and to compare the players profiles between different competitive divisions and playing positions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 20 publications
2
28
1
5
Order By: Relevance
“…In addition, it is observed that there is a decrease in the levels of BMI percentile and body fat percentage as the position of the player moves away from the goalkeeper (goalkeepers > defenders > midfielders > forwards). These results are in accordance with what was observed in higher categories (U14-U20) [21,43]; however, thanks to this study, it can be concluded that the anthropometric differences between field positions already exist from the lowest categories (U12). This outcome could be attributed to the fact that goalkeepers are subject to a lower metabolic rate than other players during games and training [18,44].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, it is observed that there is a decrease in the levels of BMI percentile and body fat percentage as the position of the player moves away from the goalkeeper (goalkeepers > defenders > midfielders > forwards). These results are in accordance with what was observed in higher categories (U14-U20) [21,43]; however, thanks to this study, it can be concluded that the anthropometric differences between field positions already exist from the lowest categories (U12). This outcome could be attributed to the fact that goalkeepers are subject to a lower metabolic rate than other players during games and training [18,44].…”
Section: Discussionsupporting
confidence: 92%
“…Because it is a recent field of study, the data on nutritional and body composition characteristics through anthropometric measures of lower-level soccer players are scarce. There are enough anthropometric data in professional teams U13-U19 [18][19][20][21], but in lower categories, the anthropometric data are limited, especially when it comes to seeing differences between field positions [21]. In addition, to date, there are no data about adherence to the Mediterranean diet in U12 professional soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…4,7 Assim sendo, a monitorização destes parâmetros torna-se uma tarefa importante em contexto desportivo. 7 Um aspeto fundamental a ter em conta aquando da avaliação da CC em futebolistas, é a posição que estes assumem em campo 7 , pois as diferentes exigências físicas 5,8 , fisiológicas 7,9 e metabólicas 7 inerentes a cada posição podem sugerir a presença de distintas características antropométricas 3,7 e de CC 7,8 entre os jogadores de uma mesma equipa 8 . De facto, a literatura tem demonstrado que existe uma especificidade posicional, tendo sido já descritas diferenças de altura 3,5 , peso 3,5 e percentagem de MG (%MG) em relação à posição assumida pelos jogadores em campo.…”
Section: Investigaçãounclassified
“…A multi-component model of body composition was used to predict skin, adipose, muscle, bone and residual tissue masses (Kerr, 1988). This method has been shown to be appropriate to determine muscle mass (Berral de la Rosa, Rodríguez-Bies, Berral de la Rosa, Rojano Ortega, & Lara Padilla, 2010) and is frequently used as fractionation method to study body composition (Bernal-Orozco et al, 2020;Holway & Garavaglia, 2009). In addition, we estimated the percentage of body fat according to the two skinfold-based equations developed by Slaughter et al (1988), which have shown to be accurate among non-obese children (Freedman, Horlick, & Berenson, 2013) and are commonly used in Colombian population due to the lack of an specific equation for this population (Alzate Salazar, Ramos Bermúdez, & Melo Betancourt, 2011;Correa & Enrique, 2008;Palma et al, 2021;Petro, Rodríguez Arrieta, & Montenegro Arjona, 2017).…”
Section: Body Compositionmentioning
confidence: 99%